1988
DOI: 10.1149/1.2095562
|View full text |Cite
|
Sign up to set email alerts
|

NMR, DSC, DMA, and High Pressure Electrical Conductivity Studies in PPO Complexed with Sodium Perchlorate

Abstract: Audio frequency electrical conductivity, DSC, DMA, and 23Na NMR measurements have been carried out on Parel 58 elastomer complexed with sodium perchlorate. [As Parel 58 is primarily po]y(propylene oxide), itwill be referred to as PPO.] The DSC and DMA measurements yield similar values for T~ which are about 72~ higher than the "central" T~ for uncomplexed PPO. In addition, the DSC studies show that the sodium perchlorate is insoluble above about 140~ The conductivity measurements have been carried out in vacuu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
7
0

Year Published

1988
1988
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(9 citation statements)
references
References 10 publications
(22 reference statements)
2
7
0
Order By: Relevance
“…Poly(propylene oxide) (PPO) is known to form amorphous ion conducting complexes with alkali metal salts. [1][2][3] Previous studies of PPQ complexed with LiClO 4 2 and NaClO 4 3 have shown that large scale segmental motion of the polymer chains is principally responsible for ionic transport, in general agreement with the results of a wide array of recent investigations. The studies in our laboratories 2 ,3 can be summarized briefly as follows.…”
Section: Introductionsupporting
confidence: 77%
See 2 more Smart Citations
“…Poly(propylene oxide) (PPO) is known to form amorphous ion conducting complexes with alkali metal salts. [1][2][3] Previous studies of PPQ complexed with LiClO 4 2 and NaClO 4 3 have shown that large scale segmental motion of the polymer chains is principally responsible for ionic transport, in general agreement with the results of a wide array of recent investigations. The studies in our laboratories 2 ,3 can be summarized briefly as follows.…”
Section: Introductionsupporting
confidence: 77%
“…Similar behavior has been observed for PPOsNaClO 4 where it was concluded that the high temperature endotherm is due to the salt coming out of the polymer. 3 The primary evidence is that only the glass transition due to uncomplexed PPO is observed after quenching from temperatures above that of the sharp endotherm. Further, the material exhibits the original behavior ( Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the softness of NaI makes it easier to attain and maintain contact with other components in the battery 28 . Investigations have also been created on Na ion conducting polymer electrolytes based on polyethylene oxide (PEO), poly(phenylene oxide) (PPO), and poly(bis‐[methoxyethoxyethoxy]phosphazene) (MEEP) complexed with NaI, NaClO 4 , NaSCN, and NaCF 3 SO 3 29‐31 . Apart from the scientific interest, the utilization of Na has many benefits over their lithium counterparts; Na is available in abundance at a less expensive value than atomic number lithium.…”
Section: Introductionmentioning
confidence: 99%
“…ILs are considered as promising green electrolytes due to their unique and excellent characteristics such as negligible vapor pressure, nonflammability, noncorrosive with high thermal stability which makes them suitable for applications as electrolytes for energy conversion, storage devices, and suitable as plasticizers. 14 20 Sodium ion–conducting polymer electrolytes based on PEO complexed with sodium hexafluorophosphate , 21 sodium thiocyanate (NaSCN), sodium iodide (NaI), sodium trifluoromethanesulfonate (NaCF 3 SO 3 ), and sodium perchlorate 22 –25 have been reported. The effect of sodium-mixed (NaI, Sodium acetate [NaCH 3 COO], and NaSCN) anion doping in PEO-based polymer electrolytes has been reported by Bhattacharya et al 26 Charge-carrier dynamics in PEO-based polymer electrolytes complexed with NaSCN have been reported by Gupta et al 27 The ionic conductivity of sodium ion–conducting polymer electrolytes based on sodium nitrate (NaNO 3 ) has been reported in the literature.…”
Section: Introductionmentioning
confidence: 99%